Association of systemic immune inflammation index with depression among adult type 2 diabetic patients in a tertiary hospital, Ethiopia, 2022 - Ali, Seid Yimam; Sadik, Mohammed Ibrahim; Seid, Ahmed Muhye; Mohammed, Awol Hassen; Yimam, Ahmed Adem; Shegere, Mekonin Meskelu; Shimels Ayele, Tesfaneh; Wako, Abdulmalik Jeben; Ibrahim, Mohamedaman Mohamedsied (Frontiers in Endocrinology, 2025)
BackgroundThe inflammatory and hormonal aspects of T2DM can influence the development or worsening of depressive symptoms. While most of the burden had due consideration, the mental health impact of T2DM such as depression is often unnoticed, undiagnosed, or untreated. Despite some studies exploring depression in Ethiopian T2DM patients, none have investigated the predictive role of the Systemic Immune inflammation Index (SII) in depression.ObjectiveThis study aimed to determine the prevalence of depression and its association with the Systemic Immune Inflammation Index (SII), socio-economic factors, and behavioral predictors among adult T2DM patients at Jigjiga University Comprehensive Specialized (JJU CS) Hospital.Methods and materialsA hospital-based cross-sectional study was conducted from Oct 3 to Nov 13/2022 at JJUSH. Depression was assessed by using the Patient Health Questionnaire (PHQ-9). A complete blood count was done to calculate SII. Data entry was conducted using Epidata version 4.6 and subsequently analyzed in SPSS-V-26. Multiple logistic regression with the backward elimination method was performed. Variables with a p-value < 0.05 were considered statistically significant at a 95% CIResultsA total of 263 T2DM patients were recruited in the study. Of these, 134 individuals (51%) were male. The overall prevalence of depression was 47.1%. Of the 263 enrolled T2DM patients, the majority, 142 (54%) had elevated SII. A multivariable logistic regression analysis indicated that high SII (AOR= 2.76), current Khat chewers (AOR= 2.83), ex-Khat chewers (AOR= 4.12), and female sex (AOR= 2.68) were identified independent predictors of depression.DiscussionThere was a high prevalence of depression among T2DM patients on follow-up at JJUSH. As well, SII, Khat chewing, and female sex were identified as predictors of depression. Therefore, relevant stakeholders should work towards control of systemic inflammation, avoidance of risky behaviors such as khat chewing, and promotion of healthy behavior particularly among females.